Increased Semantic Memorization in Children with ADHD during a Paradigm of Motor Priming: Exploratory Findings - Ana Moscoso; Clarisse Louisin; Simona Caldani; Mickael Worms Ehrminger; Mylene Fefeu; Eric Acquaviva; Richard Delorme; Maria Pia Bucci (MDPI AG, 2024)
Aim: The aim was to evaluate the effect of body actions on learning process, particularly semantic memory capabilities in drug-naïve children with attention deficit hyperactivity disorder (ADHD). Method: Thirty children had to listen to a story which was repeated three times in a row and then a fourth time five minutes later. After each listen, the child was asked what she/he remembered from the story. The whole sample was split randomly into three subgroups of equal IQ (mean 102.2 ± 12.7), age (mean age 8 ± 0.6 years), sex (ratio female to male 1:5) and severity of ADHD symptoms (34.2 ± 7.4); a G1 "Freeze" subgroup, which implied listening to the story while sitting on a chair without moving; a G2 "Minimal" subgroup, which implied listening to the story while sitting on a chair but free movement was allowed; a G3 "Prescribed movement" subgroup, which implied listening to the story standing up, while copying the experimenter movements that mimicked the actions told in the story. Results: Although our sample was limited in size, interestingly, children in the G3 subgroup showed the highest short-term semantic memory retention compared to G1. In all subgroups, repetition allowed an increase in performance. Conclusions: Our exploratory findings stress the positive role of movement in children with ADHD to increase semantic memorization. Hyperactivity may counteract the deficit of memorization related to attention impairment in children with ADHD. Our results may encourage parents or teachers to allow children with ADHD to move around during short-term memory-retention tasks.